2014
DOI: 10.1590/0104-6632.20140314s00002880
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and spray drying of lipase produced by the endophytic fungus Cercospora kikuchii

Abstract: -A lipase from the endophytic fungus Cercospora kikuchii was purified, biochemically characterized and the effects of spray drying on stabilization of the purified enzyme were studied. The lipase was purified 9.31-fold with recovery of 26.6% and specific activity of 223.6 U/mg. The optimum pH and temperature were 4.6 and 35 °C, respectively, while the Vmax was 10.28 µmol/min.mg -1 protein and Km 0.0324 mM. All the metal ions tested enhanced the enzyme activity. The lipase retained almost 100% activity in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…The last one is attractive for all types of enzymes, in particular lipases due to its use in organic media, bringing some industrial and economical advantages such as recovery and re-use, greater stability and continuous operation (Adlercreutz, 2013). So far, various carriers and methodologies have been used for enzyme immobilization in order to improve the properties of free enzyme (Castro et al, 2001;Freitas et al, 2010;Pereira et al, 2003;Costa-Silva et al, 2014a). Enzymes *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…The last one is attractive for all types of enzymes, in particular lipases due to its use in organic media, bringing some industrial and economical advantages such as recovery and re-use, greater stability and continuous operation (Adlercreutz, 2013). So far, various carriers and methodologies have been used for enzyme immobilization in order to improve the properties of free enzyme (Castro et al, 2001;Freitas et al, 2010;Pereira et al, 2003;Costa-Silva et al, 2014a). Enzymes *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have investigated the effects of carbohydrates on enzyme stability after the spray-drying process [45][46][47][48]. The samples of lipase from fungus Cercospora kikuchii were stored at temperatures 5, 25, and 40 • C for up to 6 months [45]. Costa-Silva et al [45] showed that the enzyme residual activity decreased with increasing temperature.…”
mentioning
confidence: 99%
“…The samples of lipase from fungus Cercospora kikuchii were stored at temperatures 5, 25, and 40 • C for up to 6 months [45]. Costa-Silva et al [45] showed that the enzyme residual activity decreased with increasing temperature. After stored at temperatures 5 • C for 6 months, the purified lipase in the presence of maltose, maltodextrin, and β-cyclodextrin remains over 70% residual activity.…”
mentioning
confidence: 99%
“…[3] Drying technologies can be utilized to obtain dehydrated and stable thermosensitive products like microbial enzymes. [4] On the other hand, enzyme immobilization are other mechanisms used to improve enzymes properties (like stability, activity, inhibition by reaction products and selectivity toward non-natural substrates), and allows recovery and reuse of the biocatalyst. [2] In this work, we associated the benefits of drying and immobilizing processes and performed them in a single step employing a spouted bed system.…”
Section: Introductionmentioning
confidence: 99%